EDUKASI PENCEGAHAN ADIKSI PORNOGRAFI PADA SISWA SMP MELALUI VIDEO PENDEK - Urrahman, Dhiya; Trisnaningsih, Rahma; Isnugroho, Hernawan (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2023)
ABSTRACT Pornography addiction has become a serious problem that threatens the mental health and social development of adolescents in Indonesia, including in Yogyakarta. The results of the study show that pornography addiction has a negative impact on adolescent psychosocial development, especially in Yogyakarta. This includes decreased academic achievement, impaired social relationships, and risk of mental health disorders. This service program aims to increase junior high school youth's knowledge regarding pornography addiction. This program includes counseling about the negative effects of pornography addiction, managing free time, and strengthening moral and ethical values. This educational program was delivered through health education using short video media and was attended by 68 grade VIII students of junior high school. Based on the evaluation carried out, most of the participants were very enthusiastic about participating in this community service activity. With this activity, junior high school students become more aware of the negative effects of pornography addiction. Keywords: Health Education, Pornography, Middle School Students